Earth - Van Rose, Susanna (New York : Dorling Kindersley, 2005)
Discover the secrets of the Earth from the far reaches of the atmosphere to the mysteries of the interior.
"83"--Spine.
Includes index.
Keywords: Earth sciences -- Juvenile literature; Earth sciences